The forging of nationhood - Pandey, Gyanendra, 1949-; Geschiere, Peter (New Delhi : Manohar, 2003)
Contributed articles.
The forging of nationhood : the contest over citizenship, ethnicity and history / Gyanendra Pandey and Peter Geschiere -- Citizenship and the administration of dominated populations : the case of postcolonial Ecuador / Andres Guerrero -- The spirit of Bolivian laws : citizenship, infamy and patriarchal hierarchy / Rossana Barragan -- Wrestling with the connotations of Chinese Minzu / Zhang Haiyang -- The return of Keppetipola's Cranium : the construction of authenticity in Sri Lankan nationalism / Nira Wickramasinghe -- Women's place in the nation : an early twentieth century Indian debate about the right of maidenhood / Sudhir Chandra -- Inventing oneself as "Mu-Luba" in Zaire : state, citizen, and ethnic power in modernity / T.K. Biaya -- From conquest to consent as the basis of state formation : reflections in Rawanda / Mahmood Mamdani -- The story of three songs : illuminations on the cultural politics of Thai citizenship / Kasian Tejapira.
Includes bibliographical references.
Keywords: Nationalism -- Developing countries; Cultural pluralism -- Developing countries; India